2015
DOI: 10.1007/s11325-014-1116-4
|View full text |Cite
|
Sign up to set email alerts
|

Co-upregulation of Toll-like receptors 2 and 6 on peripheral blood cells in patients with obstructive sleep apnea

Abstract: OSA patients had increased TLR2/6 co-expressions on blood immune cells, which were related to their immune cell counts and could be reversed with CPAP treatment. In vitro IHR could induce TLR2/6 co-upregulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 36 publications
(39 reference statements)
0
15
0
Order By: Relevance
“…Toll-like receptor 4 (TLR4), a typical representative of pattern recognition receptors in innate immune responses, plays an important role in activation of inflammation in atherosclerosis. It has been recently demonstrated that IHR accelerated growth and vulnerability of atherosclerotic plaque, which probably acted by triggering the activation of TLR4/NF-κB signaling [4][5][6][7]. Acting as both up-stream and down-stream mediators of TLR signaling, tumor necrosis factor (TNF)-α has been shown to be upregulated in OSA patients, and this increase became more pronounced with the more severe grades of OSAS, indicating that TNF-α might be a promising circulating biomarker for the development of OSA [8].…”
Section: Introductionmentioning
confidence: 99%
“…Toll-like receptor 4 (TLR4), a typical representative of pattern recognition receptors in innate immune responses, plays an important role in activation of inflammation in atherosclerosis. It has been recently demonstrated that IHR accelerated growth and vulnerability of atherosclerotic plaque, which probably acted by triggering the activation of TLR4/NF-κB signaling [4][5][6][7]. Acting as both up-stream and down-stream mediators of TLR signaling, tumor necrosis factor (TNF)-α has been shown to be upregulated in OSA patients, and this increase became more pronounced with the more severe grades of OSAS, indicating that TNF-α might be a promising circulating biomarker for the development of OSA [8].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with OSA show a rapid decrease in serum and plasma BDNF levels during initiation of the treatment (with PAPdevice), likely reflecting enhanced neuronal demand for BDNF in this condition. (40) Similarly, OSA patients had increased TLR2-expressions on blood immune cells, which could be reversed with PAP treatment (41). TLR2-deficiency has been shown to impair neurogenesis previously (42) and more recently, the TLR2-receptor has been shown to enhance adult neurogenesis in the hippocampal DG after cerebral ischaemia (43).…”
Section: Discussionmentioning
confidence: 98%
“…PMBC from six healthy subjects (600 μL per well, and adjusted to 1×10 6 cells per ml) were exposed to normoxia (NOX) or IHR in a custom-designed, incubation chambers which are attached to an external O2-CO2-N2 computer-driven controller, as described previously[12]. Air-phase set point consisted of a 35-min hypoxic period (0% O2 and 5% CO2), followed by 25 min of re-oxygenation (21% O2 and 5% CO2), using the BioSpherix OxyCycler C42 system (BioSpherix, Redfield, NY), 7 hours each day for 4 days.…”
Section: Methodsmentioning
confidence: 99%